Analysis of mesh router placement in wireless mesh networks using Friedman test considering different meta-heuristics. (2015) - Oda, Tetsuya; Liu, Yi; Sakamoto, Shinji; Elmazi, Donald; Barolli, Leonard; Xhafa, Fatos
In this paper, we deal with connectivity and coverage problem in wireless mesh networks (WMNs). We used Friedman test to compare genetic algorithm (GA), tabu search (TS), hill climbing (HC) and simulated annealing (SA). We found out that GA, TS, HC and SA have differences in their performance. Then, we used the implemented systems WMN-GA, WMN-TS, WMN-HC and WMN-SA to evaluate and compare the performance of the systems for different distributions of mesh clients in terms of size of giant component (SGC) and number of covered mesh clients (NCMC). The simulation results show that for uniform distribution the WMN-HC and WMN-SA perform better than WMNGA and WMN-TS. However, for small radius of communication distance, the SGC of WMN-TS is better than other systems. For normal distribution, for big radius of communication distance, the WMN-GA has the best performance. For exponential distribution, the WMN-HC and WMN-SA perform better than WMN-GA for all communication distances. For Weibull distribution, the WMN-TS has a good performance for small radius of communication distance, but for big radius of communication distances the WMN-GA, WMN-HC and WMN-SA perform better.